Analisis Pengaruh Jumlah Raw Material dan Dilution Terhadap Lama Waktu Pembuatan Sampel Fragrance Oil Pada PT XYZ Menggunakan Metode Regresi Linear Berganda - Utomo, Hagung Dika Ramanitya (Journal of Academia Perspectives, 2024)
The fragrance industry plays a pivotal role in creating captivating sensory experiences for consumers. This study focuses on PT XYZ, a leading company in the flavor and fragrance sector. The production of fragrance oil samples is a crucial stage in fragrance product development, impacting production time, quality, and costs. In this research, the number of raw material types and dilution are identified as independent variables to optimize this process. Multiple linear regression is employed to identify the relationship between the number of raw material types and dilution with the speed of fragrance sample production. The analysis results reveal that a linear model with the equation Y=1.41+0.46X1+1.28X2 is suitable for modeling this relationship. Furthermore, joint influence tests indicate that the number of raw material types and dilution collectively significantly affect the time required for fragrance oil sample production. This study not only provides insights to PT XYZ for optimizing fragrance development processes but also contributes broadly to the scientific understanding of fragrance formulation. The conclusion suggests that linear modeling can assist in estimating production time based on the variables of the number of raw material types and dilution, supporting industry efforts to enhance efficiency and product quality.